How Self-Regulation and Environmental Knowledge Shape Eco-Friendly Attitudes: Insights from Adiwiyata High School Students in Serang, Banten - Khastini, Rida Oktorida; Hendriyani, Mila Ermila; Usman, Usman; Gunawan, Yusep (FKIP Universitas Lampung, 2024)
How Self-Regulation and Environmental Knowledge Shape Eco-Friendly Attitudes: Insights from Adiwiyata High School Students in Serang, Banten. Objective: This study investigates how self-regulation and environmental knowledge influence eco-friendly attitudes among Adiwiyata High School students in Serang, Banten. Methods: A descriptive correlational approach was employed to analyze the relationships between environmental knowledge, self-regulation, and attitudes toward environmental conservation. The population comprised students from SMAN 3 Serang City (classes XI-13 and XII MIPA-2) and SMAN 1 Ciruas (classes XI MIPA-6 and XII MIPA-2). Using purposive random sampling, a sample of 150 students was selected. Data collection involved an environmental care attitude survey, an environmental knowledge exam, and a self-regulation questionnaire, all of which were validated and tested for reliability. The analysis included Pearson correlations, linear regressions, and path analysis to understand both direct and indirect effects. Findings: The results showed that the average self-regulation score was 76.25, the environmental knowledge score was 64.10, and the environmental care attitude score was 79.40. There is a positive and significant relationship between self-regulation and environmental knowledge with environmental care attitudes. Students with greater environmental awareness and self-control often exhibit more environmentally conscious attitudes. Conclusion: The findings emphasize the importance of including comprehensive environmental education programs that convey information and educate students on self-regulation skills to promote sustainable environmental behaviors. Keywords: self regulation, environmental knowledge, environmental care attitudeDOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp210-222